Development of a fully automated low‐pressure [(11)C]CO carbonylation apparatus - Ferrat, Mélodie (J Labelled Comp Radiopharm, 2020)
[(11)C]carbon monoxide ([(11)C]CO) is a versatile synthon for radiolabeling of drug‐like molecules for imaging studies with positron emission tomography (PET). We here report the development of a novel, user‐friendly, fully automated, and good manufacturing practice (GMP) compliant low‐pressure synthesis module for (11)C‐carbonylation reactions using [(11)C]CO. In this synthesis module, [(11)C]CO was reliably prepared from cyclotron‐produced [(11)C]carbon dioxide ([(11)C]CO(2)) by reduction over heated molybdenum and delivered to the reaction vessel within 7 min after end of bombardment, with an overall radiochemical yield (RCY) of 71%. [(11)C]AZ13198083, a histamine type‐3 receptor ligand, was used as a model compound to assess the functionality of the radiochemistry module. At full batch production conditions (55 μA, 30 min), our newly developed low‐pressure (11)C‐carbonylation apparatus enabled us to prepare [(11)C]AZ13198083 in an isolated radioactivity of 8540 ± 1400 MBq (n = 3). The radiochemical purity of each of the final formulated batches exceeded 99%, and all other quality control tests results conformed with specifications typically set for carbon‐11 labeled radiopharmaceuticals. In conclusion, this novel radiochemistry system offers a convenient GMP compliant production drugs and radioligands for imaging studies in human subjects.